Hailey-Hailey Disease Treated with Individualised Homoeopathy—An Evidence-Based Case Report - Dastagiri, P.; Pratap, Nirmala (Homœopathic Links, 2022)
Hailey-Hailey disease (HHD) is a rare autosomal dominant skin disorder presented as blistering dermatosis with recurrent erythematous plaques, leading to erosions, fissures and vegetations seen in the skin folds. Prevalence of this disease occurs in 1 to 4 per 100,000 affected between third and fourth decade, mostly either under-reported or misdiagnosed. Under standard conventional treatment, recurrence and remissions are typical. Therefore, it affects the quality of life compared with other skin disorders. However, with the individualised homoeopathic medicine, Psorinum, this rare case was treated without topicals; no recurrence of the complaints and adverse effects were observed in 1 year of follow-up. Furthermore, changes in the dermatology life quality of life questionnaire score from 20 (at baseline) to zero have been noticed; the modified Naranjo criteria for homeopathy total score was +9 out of +13, providing evidence attributed by the intervention. This case report reinforces that individualised homoeopathic intervention is beneficial in rare skin disorders like HHD, and pooling such data will develop future research concepts in this area.
Keywords: Hailey-Hailey disease; homoeopathy; Psorinum; dermatology life quality of life (DLQI) questionnaire; Modified Naranjo criteria for homeopathy (MONARCH)